HARMONIZATION OF ISLAMIC ECONOMIC LAW WITH LOCAL CULTURE: STUDY OF THE PETATAH-PETITIH MINANGKABAU - Arifki Budia Warman; Riska Fauziah Hayati; Wardatun Nabilah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
This paper's main problem is how to harmonize Islamic economic law with local culture, namely in petatah-petitih Minangkabau. This research departs from the Minangkabau religious customary philosophy, “Adat Basandi Syarak, Syarak Basandi Kitabullah”. Customary law and Islamic law as laws that live amid the Minangkabau society. Petatah-petitih, as a classic Minangkabau literature originating from the ancestors of the Minangkabau people, contains values to guide people in their behavior. Using literature study or documentation with qualitative descriptive research method, the research results reveal various harmonies between the values and principles of Islamic economic law with the values contained in petatah-petitih Minangkabau. Thus, the existence of petatah-petitih Minangkabau can play a role in internalizing the values of Islamic economic law in Minangkabau society. Enabling petatah-petitih Minangkabau indirectly also brings to life the values of Islamic economic law in the Minangkabau society.